2020
DOI: 10.1017/s0025315419001188
|View full text |Cite
|
Sign up to set email alerts
|

First record of vertical movements of the totoaba (Totoaba macdonaldi) as evidenced by pop-up satellite tags in the Upper Gulf of California

Abstract: The description of the movements and habitat preference of marine fishes is essential to understand their biology and in the evaluation of commercially exploited species and the conservation of endangered ones. In this regard, little is known about the movements of the totoaba (Totoaba macdonaldi), despite its being listed as critically endangered and having been a relevant fishery resource in the past century in Mexico. Totoaba is a fish species endemic to the Gulf of California characterized by late maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Numerous fish species are known to partake in DVM in response to prey behaviour, usually towards the surface at night and deeper during the day. This has been identified in at least two other sciaenid species; Totoaba macdonaldi [30] and Atractoscion nobilis [31]. In this study, a similar behaviour was observed but only during the months of September and October for fish #3, #8, #18 and #20, and during July for fish #20, which may suggest that this is related to foraging, as was the case with T. macdonaldi [30].…”
Section: Plos Onesupporting
confidence: 82%
See 2 more Smart Citations
“…Numerous fish species are known to partake in DVM in response to prey behaviour, usually towards the surface at night and deeper during the day. This has been identified in at least two other sciaenid species; Totoaba macdonaldi [30] and Atractoscion nobilis [31]. In this study, a similar behaviour was observed but only during the months of September and October for fish #3, #8, #18 and #20, and during July for fish #20, which may suggest that this is related to foraging, as was the case with T. macdonaldi [30].…”
Section: Plos Onesupporting
confidence: 82%
“…This has been identified in at least two other sciaenid species; Totoaba macdonaldi [30] and Atractoscion nobilis [31]. In this study, a similar behaviour was observed but only during the months of September and October for fish #3, #8, #18 and #20, and during July for fish #20, which may suggest that this is related to foraging, as was the case with T. macdonaldi [30]. Results regarding the summer months were mostly based on a single fish (# 20).…”
Section: Plos Onementioning
confidence: 89%
See 1 more Smart Citation
“…Totoaba were found in the estuarine habitat (spawning grounds; De Anda-Montañez et al., 2013 ) in winter and spring, in the coastal and rocky habitats (feeding areas; De Anda-Montañez et al., 2013 ) in autumn, but were not found in any of the sampled sites in summer. In summer, when sea surface temperatures in the Gulf of California can be over 28 °C, totoaba migrate to deeper (∼70 m) colder (∼21 °C) zones ( Hernández-Tlapale et al, 2020 ) being, thus, inaccessible to fishing gear. Fishes were caught with an empirical gill net (built following the knowledge and experience of the fishermen) of approximately 120 m long, 4 m wide (depth) and 10″mesh opening, as well as with individual fishing rods with number 5 hook.…”
Section: Methodsmentioning
confidence: 99%